Assessing the Effects of Isoinertial Eccentric Training on Kinetic Stability, Feinting Ability, and Kicking Power in Youth Rugby Players: A Randomized Controlled Study - Anwar Ali S Syed; William R Rajesh; S Kalaivani; R Purushothaman; Kirubakar Glady; Darling Margaret Glory (Physical Education Theory and Methodology)
Background. Rugby requires explosive strength in the lower body, agility, and stability, with eccentric actions being key in performance and in the prevention of injuries. Although isoinertial training has shown promise in enhancing eccentric strength in other sports, its effects on rugby-specific skills remain understudied.